Association between Cardiac Changes and Stress, and the Effect of Peroxisome Proliferator-activated Receptor-γ on Stress-induced Myocardial Injury in Mice - 高进辽 薛桥 王士雯 高丽菲 蓝云锋 方舟 傅义程 刘岩 李泱 范利 (Journal of Huazhong University of Science and Technology. Medical sciences, 2015)
This study was aimed to investigate the effect of stress induced by high-intensity exercises on the cardiovascular system. In the epidemiological investigation, 200 subjects（test group） engaged in special high-intensity exercises, and 97 who lived and worked in the same environment and conditions as those in the test group, but did not participate in the exercises served as controls. In the second part of the study, 50 mice were randomly divided into control group, exhaustive swimming group, white noise group, exhaustive swimming plus white noise group, and pioglitazone intervention group. The results showed that the plasma concentrations of the myocardial injury markers heart fatty acid-binding protein（H-FABP）, C-reactive protein（CRP）, β-endorphin（β-EP） and levels of psychological stress were significantly increased in test group as compared with control group; special high-intensity exercises resulted in a significant elevation of the incidence of cardiac arrhythmias. Animal experiments showed that the plasma levels of corticosterone（CORT） and troponin I（Tn I） were raised while the level of SOD was reduced in exhaustive swimming group, white noise group, and exhaustive swimming plus white noise group. The expression levels of PPARγ m RNA and protein were decreased in myocardial tissues in these groups as well. HE staining showed no remarkable change in myocardial tissues in all the groups. Treatment with pioglitazone significantly decreased the plasma levels of Tn I and CORT, while increased the level of SOD and the expression levels of PPARγ m RNA and protein. It was concluded that the high-intensity exercises may induce a heavy physical and psychological stress and predispose the subjects to accumulated fatigue and sleep deprivation; high-intensity exercises also increases the incidence of arrhythmias and myocardial injury. PPARγ may be involved in the physical and psychological changes induced by high-intensity exercises.